2016
DOI: 10.1186/s13229-016-0078-8
|View full text |Cite
|
Sign up to set email alerts
|

No relationship between early postnatal testosterone concentrations and autistic traits in 18 to 30-month-old children

Abstract: BackgroundSome previous research has suggested that testosterone prenatally contributes to gender differences in autistic traits, but little is known about the role of testosterone during early postnatal development (mini-puberty). Two prior studies found no sex difference in testosterone postnatally in saliva samples and detected little to no relationship between testosterone postnatally and autistic traits in toddlers. These findings may reflect late measurements of testosterone at 3 to 4 months of age, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…In agreement with the above theory, a couple of studies on postnatal steroids in autistic patients found significantly higher levels of androgens in saliva (Majewska et al 2014) and blood samples (Geier and Geier 2007) of autistic children. In contrast, other studies found no relationship between postnatal testosterone concentrations and autistic traits in toddlers (Auyeung et al 2012, Kung et al 2016. Together, the later findings arose hypothesis that prenatal (but not postnatal) androgen exposure is associated with the development of autistic traits in young children (Auyeung et al 2012).…”
Section: Steroids and Autismmentioning
confidence: 82%
“…In agreement with the above theory, a couple of studies on postnatal steroids in autistic patients found significantly higher levels of androgens in saliva (Majewska et al 2014) and blood samples (Geier and Geier 2007) of autistic children. In contrast, other studies found no relationship between postnatal testosterone concentrations and autistic traits in toddlers (Auyeung et al 2012, Kung et al 2016. Together, the later findings arose hypothesis that prenatal (but not postnatal) androgen exposure is associated with the development of autistic traits in young children (Auyeung et al 2012).…”
Section: Steroids and Autismmentioning
confidence: 82%
“…Two prior studies found little to no association between salivary testosterone at 3–4 months postnatal and subsequent parent‐report autistic traits in toddlers ( N = 35 in Auyeung et al., ; N = 84 in Saenz & Alexander, ). A more recent study related salivary testosterone during the peak of minipuberty at 1–3 months of age to subsequent parent‐report autistic traits and also found no relationship in either sex in a sample of 86 toddlers (Kung, Constantinescu, Browne, Noorderhaven, & Hines, ). Although these studies had relatively small samples, they converge to suggest that there is little to no association between testosterone exposure during minipuberty and autistic traits.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of differences between boys and girls in testosterone in both studies and in autistic traits in one study limits the studies' implications for the neurobehavioural effects of mini-puberty on gendered behaviour, because testosterone is hypothesized to be influential at times when it is higher in males than in females, and to influence characteristics that show gender differences. The third study measured testosterone at the peak of mini-puberty, between aged 1 to 3 months, but also found no relationship to subsequent Q-Chat scores in 39 boys, 47 girls or the entire sample of 86 children aged 18 to 30 months, although both salivary testosterone and scores on the Q-CHAT showed the expected sex / gender differences [33].…”
Section: Early Postnatal Testicular Activation: Mini-pubertymentioning
confidence: 88%